2011
DOI: 10.1097/jto.0b013e31822a75be
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Survival in Patients with Lung Cancer with Diabetes Mellitus

Abstract: Patients with lung cancer with diabetes mellitus have an increased survival compared with those without diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 19 publications
4
41
0
Order By: Relevance
“…However, this mechanism has not yet been confirmed. Notably, Hatlen et al (5) reported that patients with DM have a reduced propensity for metastatic disease and that this may partially account for the improved survival of lung cancer patients with DM. Although this previous study had a large sample size, only 4.5% of the patients with lung cancer had DM, which is lower than the prevalence of DM in middle-aged and elderly patients in developed countries (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this mechanism has not yet been confirmed. Notably, Hatlen et al (5) reported that patients with DM have a reduced propensity for metastatic disease and that this may partially account for the improved survival of lung cancer patients with DM. Although this previous study had a large sample size, only 4.5% of the patients with lung cancer had DM, which is lower than the prevalence of DM in middle-aged and elderly patients in developed countries (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Although this previous study had a large sample size, only 4.5% of the patients with lung cancer had DM, which is lower than the prevalence of DM in middle-aged and elderly patients in developed countries (16,17). In the study by Hatlen et al (5), diabetic patients were defined as those who disclosed their diabetic condition in a questionnaire and were taking medication for diabetes. In addition, the majority of patients in this previous study had very short survival, regardless of whether they had DM (42 patients; median survival, 8 months) or not (989 patients; median survival, 5 months) (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been found that good performance status (PS), disease stage, age and weight loss are strong prognostic factors in this malignancy. Although the prognostic significance of pre-existing DM in patients with lung cancer was evaluated in a number of studies [20][21][22][23][24][25][26][27], their findings were inconsistence. Three studies reported a shorter survival for patients with DM compared to those without DM [20][21][22].…”
Section: Introductionmentioning
confidence: 99%